Bioremediation of toxic metals in mining effluents by applying biosorption - Flores Vásquez, Jaime (2001)
Bioremediation is one of the methods to eliminate metallic pollutants from leach mining. Its use provide technical and economical adventages compared to ionic exchange or membranes. In bioacumulation, a type of bioremediation, metal ions are incorporated into microorganism cells, its inconvenient is necessity to prepare cultures media and special conditions to mantain biomass. On the other hand, biosorption uses natural polymers, called biopolymers; functional features of these macromolecules give them metallic adsorption capacity in predetermined conditions; some of them are algae derivatives like alginates, poliamides from hair, colagen from bond tissues or chitin and chitosan extracted from crustaceous shells. Specially chitosan could be obtained from chitin, second most abundant biopolymer in nature next to cellulose, its main source is food industry of prown, shrimp, crab and similar. Bioremediation by biosorption in chitosan case is a clean process from waste industrial materials. In Peru the main source are wastes from prown industry in our north sea coast.